2008
DOI: 10.1021/ja710380a
|View full text |Cite
|
Sign up to set email alerts
|

Metallosupramolecular Polyelectrolytes Self-Assembled from Various Pyridine Ring-Substituted Bisterpyridines and Metal Ions:  Photophysical, Electrochemical, and Electrochromic Properties

Abstract: This work presents several metallosupramolecular coordination polyelectrolytes (MEPEs) self-assembled from rigid, pi-conjugated, pyridine ring functionalized bisterpyridines and metal ions. The MEPEs are water-soluble and display different colors spanning the entire visible regions. Optical, electrochemical, and electrochromic properties of the obtained MEPEs are presented. The results show that the properties are profoundly affected by the nature of the substituents at the peripheral pyridine rings. Namely, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
235
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 328 publications
(241 citation statements)
references
References 48 publications
1
235
0
1
Order By: Relevance
“…We have designed and synthesized a new TPY ligand (L1) containing a TEG chain at the ortho-position of the peripheral pyridine ring of 6-bromo-4¢-(4-bromo-phenyl)-[2,2¢;6¢,2¢¢] terpyridine (1) 14 in good chemical yield by means of chemoselective nucleophilic substitution (Scheme 1). 15 Only one peripheral pyridine ring of TPY was substituted to prevent steric crowding in the coordination sphere.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have designed and synthesized a new TPY ligand (L1) containing a TEG chain at the ortho-position of the peripheral pyridine ring of 6-bromo-4¢-(4-bromo-phenyl)-[2,2¢;6¢,2¢¢] terpyridine (1) 14 in good chemical yield by means of chemoselective nucleophilic substitution (Scheme 1). 15 Only one peripheral pyridine ring of TPY was substituted to prevent steric crowding in the coordination sphere.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in good agreement with previously reported results. 14 In addition, the introduction of substituted TEG chain into BTPY ligands does not have a significant effect on the band gap of their corresponding MEPEs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] As a new type of EC materials, we have investigated metallo-supramolecular polymers, which are synthesized by the 1:1 complexation of metal ions (Fe, Cu, Ru et al ) and ditopic ligands such as bis(terpyridine)s and bis(phenanthroline)s. [4][5][6][7][8][9][10][11] The polymers have a specific color based on the metal-to-ligand charge transfer (MLCT) absorption. We have revealed that the appearance/disappearance of the MLCT absorption can be reversibly controlled by the electrochemical redox of the metal ions in the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…We synthesized metallo-supramolecular polymers including various metal ions such as Fe(II), Ru(II), Co(II), Cu(I), Ni(II) and Eu(III) by the complexation with bis(terpyridine)s, tris(terpyridine) or bis(phenanthroline)s [6][7][8][9][10][11][12][13][14][15][16][17][18]. The obtained polymers shows electrochromism [6][7][8][9][10][11], non-volatile memory [12], ion conductivity [13,14], vapoluminescence [15], electrochemical switching of emission [16] and DNA binding and cytotoxicity to cancer cells [17,18]. In addition to the unique properties, another advantage of the polymers is the uniform film formation property by spin-or spray-coating, because the solid-state polymers are amorphous unlike small metal complexes.…”
Section: Introductionmentioning
confidence: 99%